The learning program validity of using the ExPRession model to stimulate students’ systems thinking and numeracy skills - Haryanti, Septina Sri; Herlina, Kartini; Abdurrahman, Abdurrahman (Momentum: Physics Education Journal, 2023)
This study aims to describe a learning program using the ExPRession model which is valid in stimulating students' systems thinking and numeracy skills on the topic of light interference. The design of this research is Design and Development Research (DDR). The data from this study were in the form of validity test results which were analyzed using mixed methods (quantitative and qualitative). The results of the data analysis showed that the learning program developed obtained a score percentage of 91.1% with very valid criteria. Based on the results of data analysis, it can be concluded that the learning program with the Expression model is very valid to stimulate students' systems thinking and numeracy skills. This is because the content validity shows that the learning program using the Expression model can be applied in learning Physics in Senior High School Class XI in the even semester on the topic of Optics (Light Interference) to stimulate students' systems thinking and numeracy skills. Furthermore, in terms of media and design validity, the teaching materials in this learning program are very interactive or multimedia-based. Therefore, they can be innovations to attract interest and motivate students to learn.